Highly efficient, large area, roll coated flexible and rigid solar modules: Design rules and realization - Lucera, Luca; Machui, Florian; Kubis, Peter; Egelhaaf, Hans-J.; Brabec, Christoph (44th IEEE Photovoltaic Specialist Conference, PVSC 2017; Category numberCFP17PSC-ART; Code 136737, 2018)
Large area, roll-to-roll printed solar modules are presented in literature with power conversion efficiencies (PCE) well below hero solar cells produced in the lab. Here we show how to design a proper layout to minimize the electrical losses and how to evaluate optical losses induced by the substitution of the sputtered/evaporated electrodes with solution processable ones. Highly efficient, large area, roll-produced solar modules are then shown, achieving PCEs above 4.2% on total area on flexible and of 5.3% on glass substrates. A record-breaking geometric fill factor of 98.5% is demonstrated, thanks to ultra-fast laser structurin
Keywords: Large area modules; No losses; Organic photovoltaics; Printed photovoltaics; Simulation